Selected Cryptocurrency Returns and Capital Gains Tax - Based on the Example of Countries with Varying Degrees of Legal Regulations Concerning Cryptocurrencies - Gniadkowska-Szymańska, Agata; Olgić Draženović, Bojana; Suljic Nikolaj, Stella (Journal of Finance and Financial Law, 2022)
The purpose of the article/hypothesis: The purpose of this article is to present the impact of capital gains tax on the returns of the two most popular cryptocurrencies: BITCOIN and Ethereum Classic (ETC). Methodology: In this study, the rates of return on selected cryptocurrencies were proposed as a variable that may be affected by taxes on capital gains. The article presents a new approach to the analysis of issues related to cryptocurrencies. Results of the research: The results show that for selected countries (Hungary, Italy, Poland, the USA) there is a correlation between the tax rate on capital gains and the return on ETC. In the case of BITCON, however, there is no such a relationship.